Gold nanoparticles-oxidized multi-walled carbon nanotubes as electrochemiluminescence immunosensors. Issue 13 (13th June 2022) - Wang, Ruina; Huang, Yun; Chi, Yuwu
Abstract : AuNPs-ox-MWCNTs with strong electrochemiluminescence activity are applied to construct a immunosensor for the detection of CEA. This indicates that ox-MWCNTs as a luminescent material has a great application potential in analysis. Abstract : Oxidized multi-walled carbon nanotube/nano-gold (AuNP-ox-MWCNT) composites with strong electrochemiluminescence (ECL) activity were applied to construct a new ECL immunosensor for the detection of carcinoembryonic antigen (CEA). The immunosensor showed a linear response range of 10–100 ng mL −1 and detection limit of 0.76 ng mL −1 (at a signal-to-noise ratio of 3). The as-developed immunosensor exhibited several advantages, including being simple to fabricate and being label free. The results indicated that ox-MWCNTs as a luminescent material have great application potential in analysis.